Kinases in clathrin-mediated endocytosis. (1st August 2003) - Korolchuk, V.; Banting, G.
Abstract : The process of clathrin-coated vesicle (CCV) formation/disassembly has been studied intensively, and numerous proteins have been identified which aid this process. We have learnt a great deal about individual components of the CCV machinery, and now the ultimate aim is to elucidate the mechanisms regulating clathrin-mediated trafficking. One of the fundamental processes governing the complicated network of interactions is phosphorylation. It has been known for some time that several proteins associated with clathrin-coated vesicles are substrates for protein kinases. These proteins include clathrin, three of the four adaptor complex subunits, dynamin 1, synaptojanin 1 and the amphiphysins. However, the identities of the kinases involved in this process remained largely unknown until recently. This short review discusses advances in our knowledge of how CCV formation/disassembly is regulated by the phosphorylation/dephosphorylation cycle and the role played by specific protein kinases in that process.